2016
DOI: 10.5387/fms.2015-16
|View full text |Cite
|
Sign up to set email alerts
|

Radiation survey on Fukushima Medical University premises about four years after the Fukushima nuclear disaster

Abstract: This study was conducted on the Fukushima Medical University (FMU) premises (in Fukushima City, Fukushima Prefecture) about four years after the Fukushima Daiichi Nuclear Power Plant accident. Its objectives were (1) to create a map of the ambient gamma dose rate (air -kerma rate) distribution, (2) to evaluate the air -kerma rate originating from natural radionuclides, and (3) to investigate the effects of snow cover on changes in the air -kerma rate. This man -borne survey revealed that the air -kerma rate va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Fifty-one papers were excluded due to not fulfill the inclusion criteria, inappropriate publication types, or insufficient data. Finally, 28 articles were included in the analysis [ 11 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-one papers were excluded due to not fulfill the inclusion criteria, inappropriate publication types, or insufficient data. Finally, 28 articles were included in the analysis [ 11 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The values obtained in the car-borne survey indicate the radiation dose along paved roads, which are covered by asphalt. According to previous reports, 3,20) the observation of lower dose rates over sealed surfaces can be explained by easier removal of deposited radionuclides from them. Contamination in the air can be eliminated away more easily by rain and is also diluted by resuspension from wind, which is easier along sealed surface by concrete/asphalt rather than unsealed surface such as forested areas where contamination adheres to soil particles and plants.…”
Section: Estimation Of Absorbed Dose Rate In Airmentioning
confidence: 99%
“…23,24) However, a CF value of 0.748 Sv Gy -1 was used for a conservative dose estimation according to previous reports. 16,20) The geometric means of the annual absorbed dose in air by the surveys in 2011, 2014 and 2015 were 32, 11 and 8 mGy, respectively. Thus, the annual effective doses were estimated to be 24, 8 and 6 mSv, respectively.…”
Section: Estimation Of Annual Effective Dosementioning
confidence: 99%
“…Hedley, Roudier, and Peterson (2016) surveyed Dairy farm at Massey university, Auckland, in order to map the radioactive elements and their effects on the environment. Omori, Wakamatsu, Sorimach, and Ishikawa (2016) surveyed the Fukushima Medical University campus, Japan after the Fukushima nuclear power plant accident to create a map for gamma dose rate. Mohamed, Alghadi, and Al-Shamani (2016) measured the gamma ray in granite samples that are used as building materials within Al-Madinah Al-Munawarah, Saudi Arabia and concluded that the annual effective doses are comparatively lower.…”
Section: Introductionmentioning
confidence: 99%